Esmolol for the treatment of recurrent ventricular tachycardia - Simone Savastano; Alessandra Greco; Benedetta Matrone (Emergency Care Journal, 2016)
Cardiac arrest and electrical storm are two major emergencies. The use of beta blockers in these clinical conditions has been proposed; however, definite data about the emergency use of beta blockers in recurrent ventricular tachycardia with pulse have never been published. We report two cases of recurrent ventricular tachycardia, which were unresponsive to the standard pharmacological treatment but successfully responsive to esmolol infusion. Both cases showed a reduced left ventricle ejection fraction due to an acute myocardial infarction and to an idiopathic dilated cardiomyopathy respectively. Nevertheless, the use of esmolol was shown to be both safe and effective without inducing low output syndrome.